1955
DOI: 10.1085/jgp.39.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Ion Movement in the Squid Giant Axon

Abstract: The loss of Na22, K42, and Cl36 from single giant axons of the squid, Loligo pealii, following exposure to an artificial sea water containing these radioisotopes, occurs in two stages, an initial rapid one followed by an exponential decline. The time constants of the latter stage for the 3 ion species are, respectively, 290, 200, and 175 minutes. The outflux of sodium is depressed while that of potassium is accelerated in the absence of oxygen; the emergence of potassium is slowed by cocaine, while that of sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1958
1958
1979
1979

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 13 publications
3
29
0
Order By: Relevance
“…Shanes & Berman (1955) found that the Na influx averaged 63 p-mole/cm2 . sec in L. pealii; Caldwell et al 214 T. 1.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Shanes & Berman (1955) found that the Na influx averaged 63 p-mole/cm2 . sec in L. pealii; Caldwell et al 214 T. 1.…”
Section: Discussionmentioning
confidence: 97%
“…The sodium influx into the intact giant axons of squidhas been measured by a number of workers (Shanes & Berman, 1955;Caldwell, Hodgkin, Keynes & Shaw, 1960); the flux is insensitive to cyanide and appears to be mainly a passive flux or leak. In the present work the influx of sodium into perfused fibres (Baker, Hodgkin & Shaw, 1962a) has been studied with the object of determining how much greater the leakage is into these fibres due to the manipulative treatment they have undergone.…”
Section: Introductionmentioning
confidence: 99%
“…sec. Shanes & Berman (1955) determined the resting fluxes of labelled sodium, potassium and chloride in axons from Loligo pealii, and arrived at the following values in pmole/cm2. sec: Na influx 63, efflux 33; K influx 42, efflux 370; Cl influx 14, efflux 87.…”
Section: Determination Of Labelled Chlorideftuxementioning
confidence: 99%
“…The difficulty was eventually avoided by making measurements on extruded axoplasm, as described elsewhere (Caldwell et al 1960a, b), but not until a number of experiments had been done on intact axons. The complications encountered have some interest in their own right, and also have a bearing on the results reported by Shanes & Berman (1955). The purpose of this paper is to give a brief account of the preliminary influx determinations, and of a few experiments on the K efflux from axons into which 42K had been injected.…”
mentioning
confidence: 99%
“…Calculations by means of the Henderson-Hasselbalch equation suggest that roughly 10-8 moles of hydrogen ions would have to pass into a volume of axoplasm of 1-25 x 10-2 cm3 across the 1 cm2 of membrane surrounding it, in order to decrease the pH by 01 of a pH unit. Shanes & Berman (1955) give a figure of 42 x 10-12 mole/cm2/sec for the influx of potassium across the membrane of the giant axon of the squid Loltigo pealii. If the ease with which hydrogen ions penetrate through the membranes of squid axons were similar to that for potassium ions, the actual influx of hydrogen ion for an external pH of 6-0 would be about 6 x 1o-5 of that for potassium, i.e.…”
Section: -2 35mentioning
confidence: 99%